Perceived companies’ ethical responsibilities predicting organizational citizenship behaviors:The mediating role of psychological capital and affective commitment - Leal, Susana (2017)
This study shows how the employees’ perceptions of the ethical responsibilities of their companies predict their organizational citizenship behaviors, both directly and through the mediating role of psychological capital and affective organizational commitment. One hundred and forty eight employees working in ten organizations operating in Portugal reported their perceptions of ethical responsibilities, their psychological capital, and their affective organizational commitment. Their organizational citizenship behaviors were reported by their supervisors. The results show full mediation effects, suggesting that the employees’ perceptions about the companies’ ethical responsibilities predict organizational citizenship behaviors through the mediating role of psychological capital and affective commitment. In short: (a) employees develop higher psychological capital and affective commitment when they perceive that their companies behave ethically; (b) as a consequence, employees adopt more organizational citizenship behaviors.